Novos encontros de anofelíneos em recipientes artificiais New findings of Anopheles mosquitoes in artificial containers - Oswaldo Paulo Forattini; Iná Kakitani; Gisela Rita Alvarenga Monteiro Marques; Marylene de Brito (Universidade de São Paulo, 1998)
Assinalam-se novos encontros de anofelíneos em recipientes artificiais. Um deles diz respeito a formas imaturas de Anopheles bellator em criadouros experimentais e outro é concernente ao achado de An. albitarsis l.s., em recipiente abandonado. Tecem-se considerações sobre a pressão seletiva representada pela produção, cada vez maior, de objetos descartáveis. New findings of Anopheles mosquitoes in artificial containers are reported. In one, a plastic container served as a breeding place for Anopheles bellator larvae and, in another, four instar larvae of An. albitarsis s.l. were found in an abandoned toilet basin. Reflections are offered as to the selective pressure represented by the production, of an ever increasing scale, of disposable objects.